Antirracismo no ambiente teatral: uma análise do espetáculo Le traitement de la nuit [O tratamento da noite] (2023) - Cruvinel, Tiago de Brito (2025)
This article analyzes the québécois play Le traitement de la nuit (2023) by Evelyne de la Chenelière, directed by Denis Marleau, from the perspective of racism, when transposed to the Brazilian context. Despite the absence of negative reviews, the transposition reveals significant issues of structural racism. Using concepts from theorists such as Silvio de Almeida, Cida Bento, Sueli Carneiro, and Charles Mills, the study demonstrates how scenes from the play can be associated with situations akin to enslavement, especially in the context of domestic workers in Brazil. The research highlights how the seemingly harmless theatrical staging in the Quebecois context takes on racial connotations when contextualized in Brazil, emphasizing the need for a critical and sensitive analysis of cultural representations in different contexts.